Application of Groundwater Vistas in Modelling Groundwater Flow in Keiyo Highlands - Kiptum, C. K.; Mbakaa, P.; Mwangi, J. K. (Africa Environmental Review Journal, 2017)
Mathematical models which are based on mathematical equations are normally used to describe groundwater flow in a given area. In Keiyo Highlands, 37% of residents use shallow water wells as the sole source of water. Some of these wells run dry during the dry season and therefore a study was conducted with the aim to construct a 2D groundwater of the unconfined aquifer in the area to understand the groundwater behaviour in the study area. Conceptual model showing the positions of rivers, wells and recharge was done. Other data included hydraulic conductivity, porosity for the numerical model which was developed using MODFLOW code. The Graphical User Interface used was Groundwater Vistas. A grid of 2160 cells of sizes 140m by 80m was constructed in Groundwater Vistas. The model was calibrated manually by trial and error method for a steady state conditions during the rainy season in the study area. The transient state showed how the depths of water reduced in the wells. The amount of recharge was 0.00045 m/day, porosity 50%. The hydraulic conductivity varies from 0.05 m/day to 0.09 m/day. The model predicted the heads well under both steady state and transient state conditions. The percent errors were 0.005% and -0.4% for both steady and transient state, respectively.